Nomograms Incorporating the CNLC Staging System Predict the Outcome of Hepatocellular Carcinoma After Curative Resection - Liao, Rui; Wei, Xu-Fu; Che, Ping; Yin, Kun-Li; Liu, Lei (Frontiers in Oncology, 2022)
Purpose: Prediction models of postoperative prognosis for patients with hepatocellular carcinoma (HCC) based on the China liver cancer (CNLC) staging system after surgery are rare. This study aimed to compare the prognostic abilities of CNLC, Tumor-Node-Metastasis (TNM) 8th edition, Barcelona Clinic Liver Cancer (BCLC) staging systems in HCC after curative resection. We developed two nomograms incorporating CNLC staging system to predict the postoperative recurrence-free survival (RFS) and overall survival (OS) of HCC patients. Patients and methods: The prognostic abilities of CNLC, TNM and BCLC staging systems for HCC after curative resection were compared using the receiver operating characteristic (ROC) curves. Two nomograms incorporated five selected risk factors were constructed based on the multivariate Cox regression in the primary cohort with 312 HCC patients. It was validated with an independent validation cohort of 130 HCC patients. The predictive performance and discrimination ability of the two nomograms were further evaluated and compared with those of TNM and BCLC staging systems. Results: CNLC staging system had a higher area under the receiver operating characteristic curves (AUROC) value at both OS (AUC=0.692) and RFS (AUC=0.673) compared to that of TNM (ROC=0.667 for OS and 0.652 for RFS) and BCLC (ROC=0.671 for OS and 0.670 for RFS) staging systems. The independent predictors of OS (cirrhosis, gamma-glutamyl transpeptidase (GGT), tumor differentiation and CNLC staging system) and RFS (α-fetoprotein (AFP) and CNLC staging system), were incorporated into the two nomograms. OS and RFS nomograms consistently outperformed TNM and BCLC staging systems in the primary cohort. These results were verified by validation cohort. In the total of 442 patients with HCC, the RFS nomogram could predict early recurrence very well. Conclusion: The two proposed nomograms incorporating CNLC staging system may predict well for the outcomes of the patients with HCC after curative hepatectomy in clinical practice.